2014
DOI: 10.4236/ajps.2014.57103
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Tropical Grass for Deferment in Semi-Arid Region

Abstract: Management evaluation of Panicum maximum cv. massai (Massai guineagrass) under deferment contributes as a strategic reserve of forage in the Brazilian semi-arid region. The objective of this study was to evaluate biomass production and nutritive value of massai guineagrass in an area of thinned caatinga vegetation in two deferment periods (60 and 90 days after plot-leveling cut) and four use periods (30, 60, 90 and 120 days after the end of the rain season), in a random blocks design arranged in a split-plot (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The increase in the NDF, ADF and LIG values in function of the regrowth age was due to the plant maturing and increasing the stem ratio (Table ), which shows a higher content of structural tissue, high in fiber (Valles, Castillo, & Bernal, ). The increase in the components of cell walls has a significant effect on the reduction of the digestibility of dry matter (Lara et al, ), which can directly affect animal forage intake (Cavalcante et al, ). In the present study, in vitro digestibility of dry matter was higher than that reported by Vendramini et al (); 72% versus 67% and 69% versus 64% at 4 and 6 weeks, respectively, where the Urochloa hybrids showed higher values than the control.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the NDF, ADF and LIG values in function of the regrowth age was due to the plant maturing and increasing the stem ratio (Table ), which shows a higher content of structural tissue, high in fiber (Valles, Castillo, & Bernal, ). The increase in the components of cell walls has a significant effect on the reduction of the digestibility of dry matter (Lara et al, ), which can directly affect animal forage intake (Cavalcante et al, ). In the present study, in vitro digestibility of dry matter was higher than that reported by Vendramini et al (); 72% versus 67% and 69% versus 64% at 4 and 6 weeks, respectively, where the Urochloa hybrids showed higher values than the control.…”
Section: Resultsmentioning
confidence: 99%
“…Changes to the relative proportions of plant fractions and to nutritional composition within leaf and stem tissues may reflect diverse adaptation strategies of plants to water stress and strategies to maintain growth (Buxton and Fales, 1994;Le Gall et al, 2015). Understanding these strategies can help to identify plant traits that confer high drought tolerance on plants whilst maintaining structural and nutritional features that ameliorate effects on animal performance under drought conditions (Cavalcante et al, 2014;Tadielo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…El mayor rendimiento de MSh se obtuvo cuando se cosechó a cuatro y seis semanas y se considera que el forraje producido tendría mayor valor nutritivo, ya que, según Pérez Amaro et al (2004), a mayor proporción de hojas, el contenido de nitrógeno en la MSTT es mayor, lo cual se traduce en un forraje con mayor contenido de proteína cruda. Por el contrario, cuando existe mayor proporción de tallos en la MSTT, como sucedió cuando el forraje se cosechó cada ocho semanas durante la ELL, puede disminuir la digestibilidad y, como consecuencia, el consumo de forraje por el animal (Cavalcante et al, 2014).…”
Section: Rendimiento De Ms Y Componentes Morfológicosunclassified